PERSEDIAAN BAHAN BAKU OPTIMUM DENGAN METODE ECONOMIC ORDER QUANTITY PADA ES CHIKA HOME INDUSTRY - Nurhasanah, Nunung; Gunawan, Richard Perdana (Industrial and Systems Engineering Assessment Journal (INASEA), 2009)
Chika Ice Home Industry represents a home industry that manufactures ice candle, not having its own raw materials inventory system. The main cause is lack of implementation of the calculation method for optimal inventory control. This research focuses on establishing the optimum level of bookings for critically classified raw materials. Inventory method used to overcome these problems is the Economic Order Quantity-Model. To determine the approximate demand for the next one year, researchers uses Montecarlo simulation. The results of optimum reserve level based on - average demand during the Ice Chika one year ahead are as follows. EOQ for 60 kara coconut milk carton with an estimated total cost of IDR 13,280,000. EOQ for 40 cartons of condensed milk with an estimated total cost of IDR 9,169,000. EOQ 59 gallons of mineral water for an estimated total cost of IDR 3,631,000. By applying the Economic Order Quantity - The model then the company can determine the optimum level of ordering the materials needed during the production process for the foreseeable future.